2009
DOI: 10.1073/pnas.0810126106
|View full text |Cite
|
Sign up to set email alerts
|

The multifunctional histone-like protein Lsr2 protects mycobacteria against reactive oxygen intermediates

Abstract: Mycobacterium tuberculosis has evolved a number of strategies to survive within the hostile environment of host phagocytes. Reactive nitrogen and oxygen intermediates (RNI and ROI) are among the most effective antimycobacterial molecules generated by the host during infection. Lsr2 is a M. tuberculosis protein with histonelike features, including the ability to regulate a variety of transcriptional responses in mycobacteria. Here we demonstrate that Lsr2 protects mycobacteria against ROI in vitro and during ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
115
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(116 citation statements)
references
References 38 publications
0
115
1
Order By: Relevance
“…Thus, we anticipate finding other Lsr2-regulated genes that will be important for DNA transfer both on solid medium and in a biofilm. Indeed, transcriptional studies have shown that Lsr2 negatively regulates esx-1 genes (6,7,15), and we have demonstrated previously that Esx-1-mediated secretion negatively regulates transfer from the donor (12). However, the lsr2 mutants described in the present study were isolated in a ⌬esx-1 background, so we can rule out Lsr2 regulation of esx-1 as a factor in our experiments.…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…Thus, we anticipate finding other Lsr2-regulated genes that will be important for DNA transfer both on solid medium and in a biofilm. Indeed, transcriptional studies have shown that Lsr2 negatively regulates esx-1 genes (6,7,15), and we have demonstrated previously that Esx-1-mediated secretion negatively regulates transfer from the donor (12). However, the lsr2 mutants described in the present study were isolated in a ⌬esx-1 background, so we can rule out Lsr2 regulation of esx-1 as a factor in our experiments.…”
Section: Discussioncontrasting
confidence: 38%
“…Lsr2 was first described as an immunodominant antigen of M. leprae (24); however, it has since been shown to modulate a diverse range of processes. The resultant phenotypes of lsr2 mutants can be attributed to the ability of Lsr2 to bind DNA nonspecifically (6,7,15). Lsr2 belongs to the family of histone-like DNA binding proteins, a fact that was demonstrated by showing that lsr2 can suppress hns mutant phenotypes in Escherichia coli and that hns can suppress lsr2 mutant phenotypes in M. smegmatis (14).…”
mentioning
confidence: 99%
“…3) Using the NCBI Conserved Domain Search System (https://www.ncbi.nlm.nih.gov/ Structure/cdd/wrpsb.cgi) (86), we were able to identify a domain correlation between Mlut_10450 and an ancestral histone fold in a hyperthermophilic bacterium, Aquifex aeloicus (87). If the correlation is correct, Mlut_10450 could protect the bacterial genome against oxidative and stress damage, as described for another M. tuberculosis protein, Lsr2 (88). The association for Mlut_03760 is more tenuous and identifies a relationship with a predicted IG fold in a putative copper oxidoreductase, FixG.…”
Section: Resultsmentioning
confidence: 99%
“…4 Pathogen escapes killing mechanisms of toxic reactive oxygen or nitrogen intermediates by limiting phagocytic cells to generate these most effective anti-bacterial molecules. 5,6 Mtb contains molecular strategies to hijack trafficking pathways to prevent autophagy and the destruction of macrophages by apoptosis [7][8][9] that has been proposed to be the virulence characteristic of Mtb. Many manners, employed by Mtb, have been described to inhibit a macrophage self-death, [7][8][9][10][11] leading to the conclusion that this property must be an important one for the pathogen survival outcome.…”
Section: Introductionmentioning
confidence: 99%